STUDY OF VARIANT CHARACTERISTICS OF TERMS IN THE FIELD OF DIPLOMACY (CAHIERS MAGELLANES-NS, 2024)
Annotation: Each language has its own derivational opportunities and resources, the development of the compared languages ​​due to internal and external factors is almost the same. In all languages, there are different linguistic laws in the formation of the terminological system related to the field of diplomacy. The isomorphic and allomorphic features of the two languages ​​are determined by directly comparing the ways of creating new diplomatic lexemes in the languages ​​being compared.